Stephen King's gothic / John Sears. - Sears, John, 1965- (Gothic literary studies., 2011)
"Stephen King's Gothic reassesses this major contemporary Gothic writer through close and detailed readings of key works ranging from his earliest writings (Carrie, 'Salem's Lot, the Shining) to such recent novels as Duma Kay. Informed by and extensively applying concepts deriving from contemporary literary and cultural theory, and engaging closely throughout with King's texts and with his comments in his own critical writings and interviews, John Sears argues that King's particular revisions of major Gothic themes, writings and traditions can best be understood as being closely related to his recurrent concerns with the act and products of writing itself. These concerns, Sears suggests, are detectable throughout King's oeuvre and are structural to his Gothic vision. Key themes addressed include Gothic traditions and their connections to such related genres as science fiction, Gothic representations of time, space, and place, Gothic monstrosity, and the constitution (in King's versions of it) of Gothic writing itself."--P [4] of cover.